Demographics and risk factors for pediatric recurrent acute pancreatitis. Issue 5 (September 2021) - Gariepy, Cheryl E.; Ooi, Chee Y.; Maqbool, Asim; Ellery, Kate M.
Abstract : Purpose of review: Approximately 20–30% of children who experience one episode of acute pancreatitis will have at least one additional episode. For some children, pancreatitis recurs multiple times and in a few years is followed by the diagnosis of chronic pancreatitis. Identifying risk factors for recurrent episodes and disease progression is critical to developing therapeutic interventions. Recent findings: Obesity is driving an increase in biliary stone disease and severe acute pancreatitis. Recurrent acute pancreatitis (RAP) may lead to the development of diabetes through autoimmune mechanisms. Cystic fibrosis or CFTR-related disorders may present as RAP and CFTR modulator therapy can increase or decrease the risk of acute pancreatitis in these populations. Children with Crohn disease have a three-fold risk of acute pancreatitis over the general population while children with ulcerative colitis are at increased risk for pediatric autoimmune pancreatitis, a disorder that may be distinct from autoimmune pancreatitis described in adults. Obstructive jaundice in the absence of identified mechanical factors may be a presenting sign of pediatric autoimmune pancreatitis. Summary: Pediatric RAP is a painful condition that leads to gland destruction and functional insufficiency. Risk factors are being clarified but preventive treatments remain elusive.